Studi Tentang Manajemen Pembelajaran Dalam Peningkatan Kualitas Pembelajaran Di SDN Pakubeureum II Kecamatan Kertajati Kabupaten Majalengka - Dini Friandini Dewi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The background of this research is that in improving the quality of learning, a teachers are required to carry out learning management properly. The better the learning management is implemented, the better the quality of learning will be obtained. With the learning management skills possessed by the teacher, it is expected to be able to improve the quality of learning. The purpose of this study was to analyze and describe: 1) Implementation of learning management in improving the quality of learning; 2) The obstacles faced by teachers in carrying out learning management in improving the quality of learning; 3) Solutions made to deal with obstacles in the implementation of learning management in improving the quality of learning. The research method used in the preparation of this thesis is descriptive with a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation. The informants in this study included school principals, supervisors, teachers, and students. The results of the study show that: 1) Learning management has been carried out quite well. However, there are several aspects that need to be improved, namely the planning stage and the evaluation stage; 2) There are obstacles faced by teachers in carrying out learning management in improving the quality of learning; 3) There are solutions to overcome obstacles in implementing learning management in improving the quality of learning.